How reticulated are species? - Mallet, James; Besansky, Nora; Hahn, Matthew W (BioEssays, 2016)
Many groups of closely related species have reticulate phylogenies. Recent genomic analyses are showing this in many insects and vertebrates, as well as in microbes and plants. In microbes, lateral gene transfer is the dominant process that spoils strictly tree‐like phylogenies, but in multicellular eukaryotes hybridization and introgression among related species is probably more important. Because many species, including the ancestors of ancient major lineages, seem to evolve rapidly in adaptive radiations, some sexual compatibility may exist among them. Introgression and reticulation can thereby affect all parts of the tree of life, not just the recent species at the tips. Our understanding of adaptive evolution, speciation, phylogenetics, and comparative biology must adapt to these mostly recent findings. Introgression has important practical implications as well, not least for the management of genetically modified organisms in pest and disease control.